1997
DOI: 10.3109/02656739709023551
|View full text |Cite
|
Sign up to set email alerts
|

Lack of thermal enhancement for taxanesin vitro

Abstract: The taxanes represent a new class of clinical chemotherapeutic agents. A series of in vitro studies were independently of each other initiated in two different institutes (Amsterdam and Madison) to test the hypothesis that hyperthermia might enhance the cytotoxicity of taxanes. Clonogenic capacity experiments (Amsterdam) included the exposure of R1- and SW 1573-cells to 1, 4, or 24 h of paclitaxel with heat 43 degrees C x 60 min in the last hour of drug treatment or at 24, 48 as well as 72 h post drug treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 13 publications
2
18
0
3
Order By: Relevance
“…In fact, increased intracellular penetration at hyperthermic temperatures had been demonstrated for the taxane compounds [20], even though they acknowledged that the rate of drug penetration depends on the type of tumor cell under investigation. It is therefore not surprising that a study by Rietbroek et al [21] revealed lack of thermal enhancement of antitumor effect of taxanes. The disparity occurred from the use of different tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased intracellular penetration at hyperthermic temperatures had been demonstrated for the taxane compounds [20], even though they acknowledged that the rate of drug penetration depends on the type of tumor cell under investigation. It is therefore not surprising that a study by Rietbroek et al [21] revealed lack of thermal enhancement of antitumor effect of taxanes. The disparity occurred from the use of different tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning paclitaxel, in an in vitrostudy of murine breast cancer, Othman et al [19] found a synergistic benefit when it was used concurrently with hyperthermia at 43°C for 1 h at 10 µml/l. However, Rietbroeck et al [17] observed no thermal enhancement of paclitaxel-induced cytotoxicity with three different cell lines, with exposure temperatures of 41.8 and 43°C and drug concentrations ranging from 0.001 to 10 µ M . Leal et al [20] have studied the interaction of hyperthermia with paclitaxel in human breast adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…All studies had an exposure duration of 1 h, and the incubation temperature ranged from 41.8 to 43°C. Different drug concentrations have been studied: 50 n M [16], 0.2 to 12 µ M [17] and 0 to 50 ng/ml [18]. None of the studies found an increase of cytotoxic effects of docetaxel with hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting reports of the interaction of docetaxel with hyperthermia. In vitro studies have shown no thermal enhancement [19,20] of docetaxel at 438C. Our previous in vivo study demonstrated thermal enhancement at 41.58C [8].…”
Section: Discussionmentioning
confidence: 99%